The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1007/s10898-010-9630-9
|View full text |Cite
|
Sign up to set email alerts
|

Nonconvex quadratically constrained quadratic programming: best D.C. decompositions and their SDP representations

Abstract: Nonconvex quadratically constrained quadratic programming, Optimal D.C. decomposition, Semidefinite program, Piecewise linear approximation, Feasible solution,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…. , M} using a difference of convex (D.C.) underestimators [22,87,118]; we refer to these as αBB underestimators because they specialise the generic results of Floudas and co-workers to MIQCQP [5,6,9,65]. Anstreicher [12] has shown that, no matter the choice of α parameter, a D.C. relaxation of MIQCQP is dominated by a relaxation combining McCormick [71] envelopes and a semidefinite condition.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…. , M} using a difference of convex (D.C.) underestimators [22,87,118]; we refer to these as αBB underestimators because they specialise the generic results of Floudas and co-workers to MIQCQP [5,6,9,65]. Anstreicher [12] has shown that, no matter the choice of α parameter, a D.C. relaxation of MIQCQP is dominated by a relaxation combining McCormick [71] envelopes and a semidefinite condition.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Anstreicher [12] has shown that, no matter the choice of α parameter, a D.C. relaxation of MIQCQP is dominated by a relaxation combining McCormick [71] envelopes and a semidefinite condition. Based on this result [12], we avoid extensive computation generating the α parameters (e.g., we do not solve an LP as proposed by Zheng et al [118]). Section 4.6 presents the proposed αBB convexifications and demonstrates their importance to the GloMIQO 2 cutting plane strategy; generating αBB cuts is less computationally demanding than, for example, deriving vertex polyhedral cuts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Closely related approaches have recently been developed by Saxena et al [17] and Zheng et al [20]. In [17], the authors study the relaxation obtained by the following spectral splitting of A i :…”
Section: (2)mentioning
confidence: 99%
“…The paper [20] employs similar ideas but further solves a secondary SDP over different splittings of A i to improve the resultant SOCP relaxation quality.…”
Section: (2)mentioning
confidence: 99%
See 1 more Smart Citation